2016
DOI: 10.1038/srep23200
|View full text |Cite
|
Sign up to set email alerts
|

ROS-generating TiO2 nanoparticles for non-invasive sonodynamic therapy of cancer

Abstract: The non-invasive photodynamic therapy has been limited to treat superficial tumours, primarily ascribed to poor tissue penetration of light as the energy source. Herein, we designed a long-circulating hydrophilized titanium dioxide nanoparticle (HTiO2 NP) that can be activated by ultrasound to generate reactive oxygen species (ROS). When administered systemically to mice, HTiO2 NPs effectively suppressed the growth of superficial tumours after ultrasound treatments. In tumour tissue, the levels of proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(157 citation statements)
references
References 36 publications
3
151
0
3
Order By: Relevance
“…14A-C ). 206 The HTiO 2 NPs effectively suppressed the growth of superficial tumours after US treatment with elevated levels of proinflammatory cytokines and intense vascular damages ( Fig. 14D-F ).…”
Section: Diverse Stimulationsmentioning
confidence: 91%
“…14A-C ). 206 The HTiO 2 NPs effectively suppressed the growth of superficial tumours after US treatment with elevated levels of proinflammatory cytokines and intense vascular damages ( Fig. 14D-F ).…”
Section: Diverse Stimulationsmentioning
confidence: 91%
“…Strikingly, th tumors treated by a combination of TiO 2 NPs and ultrasound irradiation resulted in a significant inhibition of tumor growth compared with the untreated mice. Recently, long-circulating hydrophilized TiO 2 NPs (HTiO 2 NPs) were designed by You et al the authors, The authors demonstrated that, when systemically administered to mice, HTiO 2 NPs can suppress the progression of a deep side located tumor [199]. Moosavi Nejda et al [200] reported that, the increased intensity of US (20, 32, proposed water-dispersed TiO 2 NPs and SDT as a novel cure for malignant gliomas.…”
Section: Clinical Applications Of Nps Assisted Ultrasound In Cancer Tmentioning
confidence: 99%
“…In addition, these nanoparticles can cause membrane damage and lipid peroxidation. MSN accumulates in the cell nucleus, leads to DNA damage, and disturbs replication and transcription processes (29). All of these results show that MSN loaded with HpD causes cancer cells death.…”
Section: Discussionmentioning
confidence: 69%